Beowulf Clusters in computational mechanics - Yommi, Andrea (2002)
The use of clusters based on PC’s processors (usually of the Intel x86 family) became important in the treatment of large scale problems in mechanics. The size of problems in many situations of engineering interest, such as 3D fluid mechanics, requires computer power exceeding those of current workstations or PCs. The alternative of clusters allows the treatment of such problems without requiring expensive computational equipments. Clusters of microprocessors running free operating systems (like GNU/Linux) are usually referred to as ”Beowulf clusters”. A Beowulf cluster has been constructed at CIMEC-UNL and some parallel application codes are being developed. In this work we make a brief description of the cluster and the application code for computational fluid dynamics. We show some parallel performance analysis and some results of application of the cluster in the analysis of fluid dynamics problems.